Comprehensive geriatric assessment-based frailty clinic in a low middle income country: Time to act - Urza Bhattarai; Robin Maskey; Manisha Shrestha; Anusha Rayamajhi; Rohan Basnet; Arun Gautam; Bhupendra Shah; Sanjib Kumar Sharma (Aging and Health Research, 2024)
Comprehensive Geriatric Assessment (CGA) is a process of care that involves a holistic, multidimensional, interdisciplinary assessment of an older individual and has been demonstrated to be the choice of management for frailty. By 2050, it is expected that 80 % of the aging population will be living in low and low-middle income countries (LMICs). The implementation of geriatric programs is scarce in LMICs. CGA based frailty clinics could help facilitate early screening for impairment in physical and psychological capacities among pre-frail and frail older individuals allowing for suggestions for targeted interventions. Creating a sound healthcare model which addresses issues of older adults living with frailty is the need of the hour, especially in LMICs. Establishing frailty clinics in low-middle income countries could thus help to create a sustainable age-friendly healthcare model for the vulnerable and poor aging population. It is now the time to act.